ABLIM1 splicing is abnormal in skeletal muscle of patients with DM1 and regulated by MBNL, CELF and PTBP1. (18th November 2014) - Ohsawa, Natsumi; Koebis, Michinori; Mitsuhashi, Hiroaki; Nishino, Ichizo; Ishiura, Shoichi
<x xml:space="preserve">Abstract</x> Myotonic dystrophy type 1 (DM1) is an RNA‐mediated disorder characterized by muscle weakness, cardiac defects and multiple symptoms and is caused by expanded CTG repeats within the 3′ untranslated region of the DMPK gene. In this study, we found abnormal splicing of actin‐binding LIM protein 1 (ABLIM1) in skeletal muscles of patients with DM1 and a DM1 mouse model (HSALR). An exon 11 inclusion isoform is expressed in skeletal muscle and heart of non‐DM1 individuals, but not in skeletal muscle of patients with DM1 or other adult human tissues. Moreover, we determined that ABLIM1 splicing is regulated by several splice factors, including MBNL family proteins, CELF1, 2 and 6, and PTBP1, using a cellular splicing assay. MBNL proteins promoted the inclusion of ABLIM1 exon 11, but other proteins and expanded CUG repeats repressed exon 11 of ABLIM1. This result is consistent with the hypothesis that MBNL proteins are trapped by expanded CUG repeats and inactivated in DM1 and that CELF1 is activated in DM1. However, activation of PTBP1 has not been reported in DM1. Our results suggest that the exon 11 inclusion isoform of ABLIM1 may have a muscle‐specific function, and its abnormal splicing could be related to muscle symptoms of DM1.